Analysis of Customer Value and Student Loyalty Mediated by Student Satisfaction in an Accredited Private University's Faculty of Economics: An SEM-PLS Approach - Ezra Karamang; Umi Narimawati; Popo Suryana; Jaja Suteja (Dinasti Publisher, 2025)
Changes in the landscape of higher education in Indonesia in the last decade have created new challenges for private universities, especially in the Bandung Metropolitan area. Increasingly fierce competition requires educational institutions to be able to provide valuable services to students in order to not only attract prospective students, but also retain them through continuous satisfaction and loyalty. In this context, this study examines the influence of customer value on student loyalty with satisfaction as a mediating variable. The study was conducted at the Faculty of Economics and Business of an Accredited Private University in the Bandung Metropolitan area, involving 400 students as respondents. The sampling technique used cluster proportional random sampling to ensure representation from each university studied. The research instrument was a five-point Likert scale questionnaire, and data analysis was performed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) approach using SmartPLS version 4.0. The results showed that customer value was significant and positively impacted student satisfaction and directly induced student loyalty. In addition, satisfaction among students was also found to mediate between customer value and loyalty, implying that the experience and value learned through the institution play an important part in solidifying their emotional bond with the campus. High customer value not only increases momentary satisfaction but also has effects on students' commitment to complete their studies, provide positive word-of-mouth, and continue their education at the same university. These findings reinforce empirical evidence that the creation of customer value is the main foundation in building student satisfaction and loyalty. For higher education administrators, the results of this study have practical implications in the form of the need for innovative academic and non-academic service strategies, improved support facilities, and the development of meaningful learning experiences. Thus, private universities are not only able to retain students, but also increase institutional competitiveness amid increasingly dynamic higher education competition.